2008
DOI: 10.1080/00365510701528587
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine patterns after tourniquet‐induced skeletal muscle ischaemia reperfusion in total knee replacement

Abstract: Knee replacement trauma performed under ischaemia, is associated with modest systemic inflammatory reactions with no spillover of increased IL-6 from the traumatized area in the reperfusion phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
4
16
0
1
Order By: Relevance
“…In our study we found that TNFα and IL-6 were significantly elevated in serum at 10 min reperfusion as compared to baseline. This result is in line with two reports of tourniquet application in lower limb surgery, where a rise in IL-6 was shown at 2 h and 4 h reperfusion, respectively, in the draining blood of the ischemic limbs [19,32]. We also found a significant rise in the levels of IL-17 from baseline, highlighting the involvement of another pro-inflammatory molecule, which is known to induce EC to secrete cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…In our study we found that TNFα and IL-6 were significantly elevated in serum at 10 min reperfusion as compared to baseline. This result is in line with two reports of tourniquet application in lower limb surgery, where a rise in IL-6 was shown at 2 h and 4 h reperfusion, respectively, in the draining blood of the ischemic limbs [19,32]. We also found a significant rise in the levels of IL-17 from baseline, highlighting the involvement of another pro-inflammatory molecule, which is known to induce EC to secrete cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…However, no significant correlations between acute postoperative pain and TNF-α, both in serum and in synovial fluid, was found in our study. Additionally, it would be specially mentioned that we initially detected the IL-1β, which was reported as a strong pro-inflammatory cytokine [42, 43], but its level was very low and difficult to be detected in the systemic circulation, as well as in synovial fluid, even in subsequent periods following surgery, and this was also been reported by other researchers [24, 44]. …”
Section: Discussionsupporting
confidence: 59%
“…Additionally, it is still debated whether tourniquet-induced ischemia represents a substantial contributor to inflammatory response and muscle damage, as well as subsequent release of relative markers. Clementsen et al investigated the release of inflammatory cytokines, including IL-1β, IL-6, IL-8, and TNF-α, after tourniquet use in TKA, but levels of these cytokines did not change regardless of tourniquet use [44]. Laurence et al evaluated tourniquet-induced ischemia during TKA and reported that no significant difference in Mb between patients with and without tourniquet (less than 150 min), and the elevation of serum Mb associated with tourniquet was negligible [45].…”
Section: Discussionmentioning
confidence: 99%
“…[19] Tourniquet use may result in skeletal muscle ischemia-reperfusion injury, and thus increase the SIR to surgery. [20,21] However, the mean time for tourniquet use were similar between the groups in this study.…”
Section: Discussionmentioning
confidence: 51%